Implikasi Islam Untuk Pesan Iklan: Konteks Timur Tengah - Ramadini, Ulla (Jurnal Studi Agama dan Masyarakat, 2015)
Islam is the great religion and develops among the consumers all over the world. There is an evidence that the religious beliefs influence the consumers